2021
DOI: 10.1155/2021/6637554
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moxibustion on β-EP and Dyn Levels of Pain-Related Indicators in Patients with Rheumatoid Arthritis

Abstract: Background. Rheumatoid arthritis (RA) is a systemic immunodeficiency disease characterized by persistent synovial inflammation, pannus formation, and bone and cartilage destruction, resulting in joint malformations and function decline. Objective. The purpose of this study is to evaluate the effect of moxibustion on clinical symptoms and levels of pain-related indicators beta-endorphin (β-EP) and dynorphin (Dyn) in patients with RA and to explore the potential anti-inflammatory and analgesic mechanisms of moxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…The literature screening process is shown in Figure 1. (23,28,30,32,34,35,39,43,50,51). The characteristics of the included studies are shown in Table 2, and the characteristics of intervention measures are shown in Table 3.…”
Section: Literature Screen Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature screening process is shown in Figure 1. (23,28,30,32,34,35,39,43,50,51). The characteristics of the included studies are shown in Table 2, and the characteristics of intervention measures are shown in Table 3.…”
Section: Literature Screen Resultsmentioning
confidence: 99%
“…For random sequence generation, random number tables were used in 12 studies (22, 26-28, 31, 32, 35, 36, 45, 49, 50, 52), random numbers were generated by computer in 6 studies (21,23,29,37,42,48), and the remaining 14 studies (24,25,30,33,…”
Section: Results Of the Risk Of Biasmentioning
confidence: 99%
See 3 more Smart Citations